Одержання кристалів твердого розчину (Cs3Sb2Br9)1–х(DyBr3)х - Стерчо Іванна; Ivanna Stercho; Зубака Оксана; Oksana Zubaka; Кохан Олександр; Oleksandr Kokhan; Погодін Артем; Pogodin Artem; Філеп Михайло; Filep Mykhailo; Filep Mihály; Барчій Ігор; et al. (ДВНЗ Ужгородський національний університет, 2019)
Резюме. Метою дослідження було одержання кристалів твердого розчину (ТР) (Cs3Sb2Br9)1–х(DyBr3)х, вивчення його кристалічної структури та механізму утворення. Згідно літературних даних у бінарній системі CsBr–SbBr3 утворюється сполука Cs3Sb2Br9 з конгруентним характером плавлення при 864 К [18]. Авторами [19-24] досліджено системи RBr3–MBr (де R–Dy, Ce, M–Li, Na, K, Rb, Cs), які характеризуються утворенням проміжних тернарних сполук типу R3MBr6 (конгруентний характер плавлення) та M3R2Br9 (інконгруентний характер плавлення). Диспрозій (III) бромід одержують з диспрозій (III) оксиду «мокрим методом» [22,25]. Основні етапи синтезу включають розчинення оксиду в гарячій концентрованій бромідній кислоті, кристалізацію гідратованого броміду диспрозію, зневоднення та плавлення безводного броміду, а також очищення дистиляцією у вакуумі. Плавиться DyBr3 конгруентно при 1152 К, кристалізується у гексагональній сингонії, просторова група 6/mmm (194), a=10.709, c=3.744 Å, V=371.85 Å 3 [22,26-28].

Abstract. Halogen vacant-ordered double perovskite type A2B1B2X6 and A3B2X9 compounds can be used as inexpensive and highly efficient photoelectric converters of solar cells. Introduction of Dysprosium (Dy) to the structure of ternary compounds should lead to improvement of optical, especially luminescent, properties. According to the literature data, the only compound Cs3Sb2Br9 (melts congruently at 864 K) is formed in the CsBr–SbBr3 binary system, while in the CsBr–DyBr3 system two compounds Cs3DyBr6 (melts congruently at 1086 K) and Cs3Dy2Br9 (melts incongruently at 891 K) are formed. The stoichiometric amounts of Sb, Br, Dy and additionally purified by vacuum melting of CsBr were used for syntheses of Cs3Sb2Br9 and solid solutions (Cs3Sb2Br9)1-x(DyBr3)x in special two-section ampoules. Thermal studies indicated the formation of boundary solid solutions between Cs3Sb2Br9 and DyBr3 (up to 3 mol.% DyBr3). According to X-ray diffraction studies compound Cs3Sb2Br9 and solid solution (Cs3Sb2Br9)0.97(DyBr3)0.03 crystallized in trigonal singony (P-3m1), lattice parameters are a=7.9061(5), c=9.7173(6) Å, V=526.02 Å3 and a=7.9150(6), с=9.7214(7) Å, V=527.43 Å3 , respectively. The solid solution is formed by the multiple substitution of atoms / ions (3Cs+ + Sb3+) by atoms/ions 2Dy3+. Dy1 atoms are probably statistically located with Cs2 atoms in positions (1/3, 2/3, 0.6836), Dy2 atoms with Sb atoms in positions (1/3, 2/3, 0.1874). The formation mechanism of boundary solid solutions based on Cs3Sb2Br9 compound has been studied from the standpoint of crystal-chemical formulas. Vacancies (4) are formed in the cationic lattice of solid solutions (Cs3Sb2Br9)0.97(DyBr3)0.03 (crystallographic composition of (Cs294Sb197Dy5[ ]4Br900) due to iso- (3Dy→3Sb) and heterovalent (2Dy→6Cs) substitution. In the anionic lattice formed by Br– ions and their number remains constant (900). This indicates the formation of solid solution by the mechanism of substitution and subtraction (cationic sublattice), substitution (anionic sublattice). The single crystals of the ternary compound Cs3Sb2Br9 and solid solution (Cs3Sb2Br9)0.97(DyBr3)0.03 (diameter 10 mm and length 50 mm) were grown by the Bridgman method. The study of the dependence of the diffusion reflection on the wavelength R = f (λ) showed that the compound Cs3Sb2Br9 and solid solution (Cs3Sb2Br9)0.97(DyBr3)0.03 belong to direct-gap semiconductors, band-gap Eg = 2.55 eV (λ = 486 nm), Eg = 2.59 eV (λ = 479 nm), respectively.
Obtaining of single crystals (Cs3Sb2Br9)1–х(DyBr3)х solid solution
Keywords: тверді розчини; кристалічна структура